(3ebGeGJ GdMQjQjs - (3GdbGSe Hf Ydj Hf eMeO Hf YKeGf, CHh eMeO GdMQjQj GdHUQj , J (B516 (3g` s ((3eUQ s)
(3ChdgG (B:s
(3Gddge EfG fMeOc Ydi eG YdeJ ef GdHjGf hCdgeJ ef GdJHjGf hHYO aEfg LQi HHYV CfOjI GdCOH GdPi QcOJ ai gP GdYUQ PcQ GdebGeGJ GdJi CHJOYgG HOjY GdReGf s
(3BNQgG (B:s
(3bGd GdTjN GdQFjS gPG BNQ GdebGeGJ GdJi CfTCJgG HGdEYJRGR hCfG CSJZaQ Gddg JYGdi eeG ChLOYJg ajgG ef EHGWjd GddZh Efg Cgd GdJbhi hCgd GdeZaQI hhdi GdNjQGJ ai GdOfjG hGdBNQI JeJ GdebGeGJ GdNeShf s
(3GdfSNI HgG MhGTs
(3fSNgG GdfGSN ef CUd CHj YHO Gddg eMeO Hf HQis
(3hYdjgG bQGAI ef GdfGSN Ydi Hf HQi s
(3bQf GdfSN (B:s
(3GdbQf GdSGOSs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdCOHs